Pengaruh Model Cooperative Integrated Reading and Composition (Circ) Terhadap Hasil Belajar Membaca Siswa - Amalia Ika Suci; Moh Yamin (Journal of Elementary School (JOES), 2022)
This study aims to determine the influence of learning outcomes Indonesian using the CIRC (Cooperative Integrated Reading and Composition) learning model on the learning outcomes of reading Indonesian in class IV students at SDN Duri Kepa 07. This research uses a quantitative approach with a Quasi Experimental method type Posttest-Only Control Group Design. The population in this study was all grade IV students of SDN Duri Kepa 07 in the even semester of the 2021-2022 academic year. The study sample totaled 62 learners from classes IV-A and IV-C. The sampling technique of this study used the Cluster Random Sampling method. The research instrument is in the form of an objective test in the form of multiple-choice questions consisting of 30 questions. The instrument was first tested at SDN Duri Kepa 07 with 32 students. The calculation of the validity test uses the Correlation Point Biserial formula on 40 questions in multiple choice form with 30 valid questions and 5 drop questions. Meanwhile, in the calculation of the reliability test using KR-21, it obtained a rcount of 0.70 with a very strong level of reliable interplay. Furthermore, there is an analysis requirement test that is carried out a normal test with the liliefors formula, then normally distributed data from the experimental class and the control class are obtained. Furthermore, the homogeneity test calculation using the Fisher test obtained homogeneous distribution group variance data. Then the hypothesis test using the t-test resulted in a calculation of 2.288 with a significant 5% which resulted in the rejection of H0. The results of this study can be concluded that there is an influence of the Cooperative Integrated Reading and Composition (CIRC) model on reading learning outcomes Indonesian Grade IV students of SDN Duri Kepa 07. Keywords: CIRC Model, Reading, Indonesian Learning Outcomes